The Sander parallelogram illusion dissociates action and perception despite control for the litany of past confounds. (January 2018) - Whitwell, Robert L.; Goodale, Melvyn A.; Merritt, Kate E.; Enns, James T.
Abstract: The two visual systems hypothesis proposes that human vision is supported by an occipito-temporal network for the conscious visual perception of the world and a fronto-parietal network for visually-guided, object-directed actions. Two specific claims about the fronto-parietal network's role in sensorimotor control have generated much data and controversy: (1) the network relies primarily on the absolute metrics of target objects, which it rapidly transforms into effector-specific frames of reference to guide the fingers, hands, and limbs, and (2) the network is largely unaffected by scene-based information extracted by the occipito-temporal network for those same targets. These two claims lead to the counter-intuitive prediction that in-flight anticipatory configuration of the fingers during object-directed grasping will resist the influence of pictorial illusions. The research confirming this prediction has been criticized for confounding the difference between grasping and explicit estimates of object size with differences in attention, sensory feedback, obstacle avoidance, metric sensitivity, and priming. Here, we address and eliminate each of these confounds. We asked participants to reach out and pick up 3D target bars resting on a picture of the Sander Parallelogram illusion and to make explicit estimates of the length of those bars. Participants performed their grasps without visual feedback, and were permitted to grasp the targets after making their size-estimates to afford them an opportunity to reduce illusory error with haptic feedback. The results show unequivocally that the effect of the illusion is stronger on perceptual judgments than on grasping. Our findings from the normally-sighted population provide strong support for the proposal that human vision is comprised of functionally and anatomically dissociable systems.